Metaphors in the Translation of English Technical Texts into Malay: A Preliminary Study - Abdullah, Sharmini; Shuttleworth, Mark (Journal of Asian Scientific Research, 2013)
Effective and skilful translation of technical texts is not easy to achieve. A translator of technical texts often has to manage the selection of appropriate equivalents such as words, terms, styles, descriptions, proper exposition, discussion and presentation of the scientific concepts and ideas in the target language. This paper is a preliminary study that investigates the extent to which metaphors are used in the translation of English to Malay technical texts the study highlights particular challenges in translating technical texts from English to Malay with the focus on the use and translation of metaphors. Metaphor is significant as it opens alternatives for both translators and authors to present the required information to be in a manner that is more reader-friendly. The discussion of this paper not only centres on metaphors playing an important role in the explanation of scientific and technical concepts but also investigates the extent to which metaphors are used in the translation of English to Malay technical texts. The discussion will look into the hypothesis on how the usage of metaphors in the ST (source text) compares to that in the TT (target text). The analysis will indicate the main ways in which metaphorical expressions are rendered from English to Malay.